Identification and Characterization of Carnitine Palmitoyltransferase 1 (cpt 1) Genes in Nile Tilapia, Oreochromis niloticus. (March 2020) - Bayır, Mehtap; Arslan, Gökhan; Bayır, Abdulkadir
Four cpt 1 genes ( cpt 1α1a, cpt 1α2a, cpt 1α2b, and cpt 1β ) were identified in the Nile tilapia genome. Two transmembrane helix domains (TMH) were identified for Cpt 1α1a, Cpt 1α2a, and Cpt 1β, while Cpt 1α2b had only one TMH domain. Evidence was found of conserved gene synteny between cpt 1 genes from Nile tilapia and the cpt 1/CPT 1 genes of zebrafish and human. Phylogenetic analysis showed that Nile tilapia Cpt 1 sequences clustered in distinct clades with their orthologous Cpt 1/CPT 1 from other vertebrates. Nile tilapia cpt 1α1a, cpt 1α2a, cpt 1α2b, and cpt 1β contain 18 coding exons encoding polypeptides of 771, 784, 788, and 786 amino acids in length, respectively. The cpt 1 genes were determined in all the tested tissues with varying tissue distribution patterns. These findings suggest that (1) cpt 1α1a, cpt 1α2a, and cpt 1α2b arose in the Nile tilapia genome as a result of the teleost-specific whole-genome duplication; (2) nonfunctionalization is the most likely cause of the loss of cpt 1α1b in the Nile tilapia genome; (3) the different tissue-specific transcription of cpt 1α2a and cpt 1α2b may be either due to the sub- or the neo-functionalization of transcriptional control side.